Análisis de la sostenibilidad y competitividad de las empresas turísticas de alimentos y bebidas del cantón Sigchos, provincia de Cotopaxi. - Cajía Cajamarca, Félix Paúl (2023)
The research project is aimed at the sustainable and competitive analysis of the food and beverage tourism companies of the Sigchos canton, for that the methodological process was through interviews with the owners or managers of 8 companies where in the first objective information was collected. of the current level at which these businesses are located, for that the data collection instruments were the author's InnovaRSE methodology (Navarra, 2016), which has 30 statements, 10 for each of the dimensions that are: economic, environmental and social, for the sustainable analysis resulting in 3 companies that are moderately sustainable and 5 companies that do not have sustainability, there are several reasons such as poor management of resources, they do not have trained personnel, they do not manage environmental plans; In the second objective, data was collected that are aimed at measuring competitiveness, for which we worked with the author's BID methodology (Saavedra García, 2020), which investigates through areas and subareas within the companies, the results in the The establishments are as follows: 2 companies have medium competitiveness and the remaining 6 are in a range of low competitiveness, the reason for this is that it does not have a business organization, it is not divided by areas and sub-areas, it does not have training for personnel in areas of quality, they do not adapt to new trends in the current market among others. During the course of the research, the quantitative exploration modality was used.